2023
DOI: 10.3390/metabo13020303
|View full text |Cite
|
Sign up to set email alerts
|

Association of Red Blood Cell Distribution Width and Neutrophil-to-Lymphocyte Ratio with Calcification and Cardiovascular Markers in Chronic Kidney Disease

Abstract: We aimed to investigate the association between Red Blood Cell Distribution Width (RDW) and Neutrophil-to-Lymphocyte Ratio (NLR), simple, rapidly assessed markers from the complete blood count with vascular calcification (VC)/stiffness and cardiovascular disease (CVD) in chronic kidney disease (CKD). Dephosphorylated, uncarboxylated matrix Gla-protein (dp-ucMGP), and central/peripheral hemodynamics’ parameters were measured in 158 CKD patients, including Hemodialysis and Peritoneal Dialysis. Spearman’s rho ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…Several studies have studied the relationship of blood composite scores with CV disease in the general population. In a report of 158 patients with chronic kidney disease, red blood cell distribution width correlated with CRP, central diastolic blood pressure, and albuminuria [20]. Additionally, NLR correlated with the duration of cardiovascular disease, CRP, central diastolic blood pressure, and glomerular filtration rate.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Several studies have studied the relationship of blood composite scores with CV disease in the general population. In a report of 158 patients with chronic kidney disease, red blood cell distribution width correlated with CRP, central diastolic blood pressure, and albuminuria [20]. Additionally, NLR correlated with the duration of cardiovascular disease, CRP, central diastolic blood pressure, and glomerular filtration rate.…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, NLR correlated with the duration of cardiovascular disease, CRP, central diastolic blood pressure, and glomerular filtration rate. The authors concluded that red blood cell distribution width and NLR could serve as predictors of traditional and novel markers of vascular calcification and CV disease [20]. Similarly, in a study that enrolled 74 patients, calcium kidney stones were associated with higher levels of inflammatory biomarkers, including NLR, MLR, and SIRI, compared with ageand sex-matched non-stone formers [21].…”
Section: Discussionmentioning
confidence: 96%
“…An analysis of recently published articles reveals that among these inflammatory markers, NLR, MLR, PLR, and SII have emerged as valuable predictors of vascular disease. Numerous works have highlighted their predictive potential in this context [ 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic kidney disease (CKD) dramatically increases the risk of cardiovascular disease (CVD); this risk is rising in parallel with the deterioration of kidney function [ 1 , 2 ]. Emerging factors linked to kidney dysfunction, such as inflammation, oxidative stress, and most notably vascular calcification (VC), are gaining recognition for their critical role in CVD and reduced patient survival [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%